The Role of Teachers in Early Childhood Character Education at Syalom Bunuraya Kindergarten - Ginting, Yosicha Br; Eza, Gita Neoveri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Role of Teachers in Early Childhood Character Education at Syalom Bunuraya Kindergarten is divided into 3 roles, namely the role of teachers as educators, guides and models. This study aims to describe the role of teachers as educators, guides and models in early childhood character education at Syalom Bunuraya Kindergarten. The method used in this study is qualitative descriptive. This research will be conducted from September 11 to November 11, 2023. The source of this research is Syalom Bunuraya Kindergarten class teachers as many as 2 teachers, the subject of this research is based on teachers who have different educational backgrounds including graduates of S1 SE (Bachelor of Economics) S1 S.Pd (Bachelor of Education). Data collection techniques include non-participant observation and guided interviews. Data Analysis Data uses Milles and Humberman data analysis with data collection stages through data reduction, data presentation, and drawing conclusions. Data validity testing is performed by triangulation. The results showed that: 1. the role of teachers as educators in Syalom Bunuraya Kindergarten as protectors, companions, servants,. 2. The role of the teacher as a guide as a director, controller, monitor, bodyguard, and reminder.3. The role of the teacher as a model aligns speech with deeds and displays a neat appearance and manners inside and outside school. The obstacles faced by teachers as educators are teachers who consider all children's characteristics equally both interests, talents and skills, and cognitive are the main factors, namely calistung to support their education in elementary school as a teacher guide who do not graduate from S1 PAUD so that their knowledge is less extensive about the child's world. As a model, teachers are inconsistent with the role they play by looking immodest by wearing dresses to school.